2018
DOI: 10.3390/coatings8100336
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulation of Temperature and Stress Field for Laser Cladded Nickel-Based Amorphous Composite Coatings

Abstract: In this paper, a nickel-based amorphous composite coating was obtained on the carbon steel surface by the laser cladding process. The thermal field and stress distribution were simulated by using ANSYS finite element software where the moving heat source and powder feeding were modelled by the “Element birth and death” method. The simulation results were verified by comparing the cross-sectional profile of fusion lines and X-ray stress measurements, respectively. The results on thermal field showed that the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Therefore, determining how to reduce the deformation of thin-walled parts during laser cladding repair has become the focus of a body of research. The formation reason and action rules of stress and deformation in laser cladding are very complex, and many experts and scholars have conducted many related investigations on this topic [16][17][18][19][20][21][22]. Wang et al [23] used different types of lasers to study the properties of formed AISI316L stainless steel thin-walled parts, and found that the ultimate tensile strength of the sample produced by a pulse laser was higher than that of the sample produced by a continuous-wave laser.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, determining how to reduce the deformation of thin-walled parts during laser cladding repair has become the focus of a body of research. The formation reason and action rules of stress and deformation in laser cladding are very complex, and many experts and scholars have conducted many related investigations on this topic [16][17][18][19][20][21][22]. Wang et al [23] used different types of lasers to study the properties of formed AISI316L stainless steel thin-walled parts, and found that the ultimate tensile strength of the sample produced by a pulse laser was higher than that of the sample produced by a continuous-wave laser.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous studies [ 26 , 27 ] to determine the specific thermal conductivity of the probes, a series of steady-state numerical simulations, fed with the experimental data obtained from the thermal images, was carried out using the ANSYS Workbench (by ANSYS Inc., Canonsburg, PA, USA) software. The process is shown in Figure 6 and can be described as follows: The profile of the temperature on the upper surface of the probe was extracted from the thermographic image of the stationary setup, fitted using the optimal polynomial function, and set as a boundary condition in the simulation.…”
Section: Methodsmentioning
confidence: 99%
“…The powder flow convergence is shown in the simulations; these results are very important to present the machining effect. The thermal parameters of the additive forming parts are also necessary to be simulated to get results of the temperature and equivalent stress [11][12][13][14][15].…”
Section: Of 21mentioning
confidence: 99%